Recurrent Cherubism in an Adult Patient. Issue 3 (May 2015) - Demirtas, Nihat; Barut, Oya; Ozcan, Ilknur; Bayer, Suzan; Kazancioglu, Hakki Oguz
<x xml:space="preserve">Abstract</x> Abstract Cherubism is an uncommon, nonneoplastic, fibro-osseous disorder of the jaws in childhood and adolescence. It affects the jaw bones by deforming the cortical shell. Clinical features include progressive painless and mostly bilateral expansion of the mandible and/or maxilla. Because fibrous connective tissue replaces osseous tissue, radiographic features generally include expansile osteolytic lesions and a ground-glass appearance. Several treatment protocols for cherubism have been recommended in the literature; however, despite surgical curettage treatment, recurrences may occur. Our aim was to emphasize the high recurrence rate of cherubic lesions. In this article, we present cherubism in a young girl that relapsed after 5 surgical operations before her appearance to our clinic.